Atmosphere-driven ice sheet mass loss paced by topography: Insights from modelling the south-western Scandinavian Ice Sheet. (1st September 2018) - Åkesson, Henning; Morlighem, Mathieu; Nisancioglu, Kerim H.; Svendsen, John Inge; Mangerud, Jan
Abstract: Marine-terminating glaciers and ice streams are important controls of ice sheet mass balance. However, understanding of their long-term response to external forcing is limited by relatively short observational records of present-day glaciers and sparse geologic evidence for paleo-glaciers. Here we use a high-resolution ice sheet model with an accurate representation of grounding line dynamics to study the deglaciation of the marine-based south-western Norwegian sector of the Scandinavian Ice Sheet and its sensitivity to ocean and atmosphere forcing. We find that the regional response to a uniform climate change is highly dependent on the local bedrock topography, consistent with ice sheet reconstructions. Our simulations suggest that ocean warming is able to trigger initial retreat in several fjords, but is not sufficient to explain retreat everywhere. Widespread retreat requires additional ice thinning driven by surface melt. Once retreat is triggered, the underlying bedrock topography and fjord width control the rate and extent of retreat, while multi-millennial changes over the course of deglaciation are modulated by surface melt. We suggest that fjord geometry, ice-ocean interactions and grounding line dynamics are vital controls of decadal-to centennial scale ice sheet mass loss. However, we postulate that atmospheric changes are the most important drivers of widespread ice sheet demise, and will likely trump oceanic influence on future ice sheet mass loss and resulting sea level rise over centennial and longer time scales. Highlights: Fjord geometry controls deglacial retreat history of western Norway. Ocean warming triggers initial grounding line retreat. Sustained atmospheric warming required to drive long-term deglaciation. Individual fjord glaciers retreat out-of-phase with climate forcing.